2023
DOI: 10.1177/09716858231172440
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship Between Organizational Culture and Psychological Capital and Its Impact Using Systematic Literature Review

Abstract: The article discusses the relationship between organizational culture and psychological capital through a systematic literature review. The exploratory research methodology is adopted to identify and study the existing gap in the available literature on the relationship between organizational culture and psychological capital from year 2000 to 2021. The articles from the ‘Scopus’ and ‘Web of Science’ databases were selected for the review. The literature review mentions a positive interplaying role between org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Ref. [38] examined the relationship between organizational culture and Psychological Capital (Psy-Cap) through a systematic review, where they found a positive interaction that influences factors such as job happiness, performance, organizational behavior, and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [38] examined the relationship between organizational culture and Psychological Capital (Psy-Cap) through a systematic review, where they found a positive interaction that influences factors such as job happiness, performance, organizational behavior, and innovation.…”
Section: Introductionmentioning
confidence: 99%